Reversing Bacterial Resistance to Antibiotics by Phage-Mediated Delivery of Dominant Sensitive Genes - Edgar, Rotem (American Society for Microbiology, 2012)
Pathogen resistance to antibiotics is a rapidly growing problem, leading to an urgent need for novel antimicrobial agents. Unfortunately, development of new antibiotics faces numerous obstacles, and a method that resensitizes pathogens to approved antibiotics therefore holds key advantages. We present a proof of principle for a system that restores antibiotic efficiency by reversing pathogen resistance. This system uses temperate phages to introduce, by lysogenization, the genes rpsL and gyrA conferring sensitivity in a dominant fashion to two antibiotics, streptomycin and nalidixic acid, respectively. Unique selective pressure is generated to enrich for bacteria that harbor the phages carrying the sensitizing constructs. This selection pressure is based on a toxic compound, tellurite, and therefore does not forfeit any antibiotic for the sensitization procedure. We further demonstrate a possible way of reducing undesirable recombination events by synthesizing dominant sensitive genes with major barriers to homologous recombination. Such synthesis does not significantly reduce the gene's sensitization ability. Unlike conventional bacteriophage therapy, the system does not rely on the phage's ability to kill pathogens in the infected host, but instead, on its ability to deliver genetic constructs into the bacteria and thus render them sensitive to antibiotics prior to host infection. We believe that transfer of the sensitizing cassette by the constructed phage will significantly enrich for antibiotic-treatable pathogens on hospital surfaces. Broad usage of the proposed system, in contrast to antibiotics and phage therapy, will potentially change the nature of nosocomial infections toward being more susceptible to antibiotics rather than more resistant.